Effects of temperature and dietary protein on the growth performance and IGF‐I mRNA expression of juvenile mirror carp (Cyprinus carpio). (29th January 2015) - Huang, J.F.; Xu, Q.Y.; Chang, Y.M.
Abstract: Juvenile mirror carp were fed with five different diets containing 303, 322, 341, 361 and 379 g kg −1 protein and reared at three different water temperatures (18, 23 and 28 °C) for 60 days. We investigated the insulin‐like growth factor I ( IGF‐I ) mRNA expression, growth performance and the relationship between IGF‐I mRNA expression and the growth performance. The results indicated that the IGF‐I mRNA expression, final body weight, specific growth rate (SGR) and feed efficiency (FE) were enhanced significantly with increasing dietary protein levels ( P  <   0.05), whereas the protein efficiency ratio, hepatosomatic index (HSI) and viscerosomatic index (VSI) were decreased. Moreover, the IGF‐I mRNA expression, final body weight and SGR were increased significantly with temperature, whereas the HSI and VSI indices were decreased significantly with temperature. Correlation analysis showed that the IGF‐I mRNA expression levels in the brain and liver were positively related to the SGR and FE growth indices ( P  <   0.01). Finally, the optimal protein requirements for fish growth in different seasons were determined based on the values of SGR and FE, that is 343–348 g kg −1 protein at 18 °C, 354–352 g kg −1 at 23 °C and 371–362 g kg −1 at 28 °C. In this way, we can adjust the dietary protein levels according to culture temperature to reduce any negative impacts on dietary costs and environmental pollution.